50 let svobode gibanja delavcev in 60 let povezovanja sistemov socialne varnosti v Evropski uniji - Strban, Grega (Delavci in delodajalci, 2019)
One of the fundamental freedoms of the EU's internal market is the free movement of workers, starting at the very beginning of the creation of the original European Communities. Coordination of the social security system is necessary in order for this freedom to be realized. Its purpose is to promote the free movement of persons within the EU and to prevent individuals from losing benefits from the social security system if they exercise their right to free movement. Through the outline of the beginning and further development, the contribution intends to mark two anniversaries - 50 years of freedom of movement for workers and 60 years of coordination of social security systems.
Keywords: freedom of movement for workers; koordinacija sistemov socialne varnosti; social security; social security coordination; socialna varnost; svoboda gibanja delavcev